Factors influencing groundwater contamination near municipal solid waste landfill sites in the Qinghai-Tibetan plateau - Dan Zeng; Guanyi Chen; Peng Zhou; Hui Xu; A. Qiong; Bu Duo; Xuebin Lu; Zaimin Wang; Zhiyong Han (Ecotoxicology and Environmental Safety, 2021)
Effective management of municipal solid waste (MSW) is essential for the conservation of ecosystems in the Qinghai-Tibetan Plateau (QTP). Considering the landfill is the major method of MSW management, the factors influencing groundwater contamination near MSW landfill sites in the QTP were studied, based on field investigations, environmental impact assessment, and meteorological and hydrogeological analyses. Results indicated that the groundwater was contaminated heavily by nitrate (PI = 7.5), particularly in the landfill without an anti-seepage system, followed by nitrite (PI = 3.5) and heavy metals including arsenic (PI = 4.1) and hexavalent chromium (PI = 2.8). Total hardness, total dissolved solids, nitrate, and lead in the groundwater near the investigated landfill sites were significantly different between the monsoon and the cold seasons. Both the rainfall infiltration and the leachate infiltration were considerably limited by environmental characteristics in the QTP, including high evaporation, low rainfall, and the presence of permafrost. Soil sample contamination near landfill sites was considered as moderate (28.6% of the soil samples) and moderate to heavy (71.4% of the soil samples), based on the geoaccumulation index of mercury. However, comparatively low generation and concentrations of leachate and good topsoil quality (PI = 0.84) reduced the quantity of pollutants infiltrating into the groundwater. The alkaline leachate (pH = 7.45–9.23) and soil (pH = 7.08–8.72) also considerably decreased the concentrations of contaminants dissolved in the infiltrated rainfall and leachate. Additionally, low groundwater level can delay preferential ﬂow and enhance attenuation. Therefore, the groundwater contamination near the landfill sites was simply point pollution, which was influenced by leachate, soil, climate, and hydrogeology characteristics in the QTP. The anti-seepage system is a potential strategy for use in the prevention of groundwater contamination by MSW landfills in the QTP.